THE KINEMATIC STRUCTURE OF THE MECHANISM OF THE EXOSKELETON - MALYUGA, Oleg Vladimirovich (Вопросы экологии, 2019)
The urgency of the development of robotic exoskeletons is substantiated. The task of synthesis of the kinematic scheme of the Executive mechanism of the exoskeleton is set and possible approaches to its solution are defined. The results of kinematic scheme synthesis obtained in CATIA and SolidWorks software systems are presented. The expediency of kinematic synthesis in the SolidWorks software package using anthropometric data proposed by the CATIA software package is substantiated. The obtained ranges of changes in the generalized coordinates of the joints of the actuator, equipped with electrohydraulic servo drives, are compared with similar ranges for humans. The rapid development of robotics is explained by the need to increase productivity and improve the efficiency of work performed in various fields of human activity, among which the leading place is occupied by work in extreme conditions. This includes the elimination of the consequences of man-made and natural disasters, as well as the solution of problems associated with the manipulation and transportation of special- purpose cargo in the military field.